2015
DOI: 10.1021/acscatal.5b00475
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Model for a Metal–Organic Framework: High-Spin Rebound Mechanism in the Reaction of the Oxoiron(IV) Species of Fe-MOF-74

Abstract: We performed ONIOM QM/MM calculations to understand how ethane is hydroxylated and ethanol is converted to acetaldehyde by an oxoiron(IV) species generated within an iron-containing metal−organic framework called Fe-MOF-74. The calculations showed that the ethane hydroxylation proceeds via a high-spin rebound mechanism. The conversion of ethanol into acetaldehyde should occur more favorably via H-abstraction from the O−H bond than via C−H cleavage, although the O−H bond of ethanol is stronger than the C(1)−H b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 50 publications
4
64
0
Order By: Relevance
“…34 As displayed in Scheme 1, the rebound mechanism is a two-step process where initially one H-atom is abstracted from CH 4 , before the C-O bond is formed, while the concerted mechanism only contains one 4 reaction step and transition state. As we were not able to find a possible concerted path, in agreement with other reports in the literature, 30 we focus on the rebound mechanism. All the structural details are given in Fig.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…34 As displayed in Scheme 1, the rebound mechanism is a two-step process where initially one H-atom is abstracted from CH 4 , before the C-O bond is formed, while the concerted mechanism only contains one 4 reaction step and transition state. As we were not able to find a possible concerted path, in agreement with other reports in the literature, 30 we focus on the rebound mechanism. All the structural details are given in Fig.…”
supporting
confidence: 79%
“…For adsorption of methane a straight Fe-O-C angle has been suggested in previous studies in zeolites. 30 However, we find a strongly tilted geometry with an Fe-O-C angle of about 145 6 about 8 kJ/mol needs to be overcome for the second transition state. The total reaction is highly exothermic with an energy gain of more than 150 kJ/mol for the adsorbed methanol compared to the initially adsorbed methane molecule.…”
mentioning
confidence: 70%
“…In the meantime, Hirrao et al [57] and 4-pyridyl functionalized groups on different linkers such as using methanol, pyridine, formate, benzoate anion, and the imidazole anion. The authors concluded that the population of the d-orbital was significantly influenced by the coordination ligand field.…”
Section: Density Functional Theorymentioning
confidence: 99%
“…Quantum-mechanical calculations have predicted that magnesium-diluted MOF-74 catalyses the oxidation of ethane in the presence of N 2 O. 41 Similar calculations have also proposed that MOF-74 containing an Fe(IV)O species (CPO-27-Fe) can hydroxylate ethane to ethanol, 42 as these framework materials have been shown to separate mixtures of light hydrocarbons at their Fe(II) coordination sites 43 and to produce phenol with efficiencies as high as 60% using H 2 O 2 as an oxidant. 44 Recent studies have reported results concerning the oxidation of methane to methanol catalysed by Cu-Oxo clusters stabilized in NU-1000 MOFs, 45 and of MOFs with design inspired to particulate methane monooxygenase (pMMO).…”
Section: Introductionmentioning
confidence: 96%